The effect of clay particles on the efficacy of a biocide - Pereira, MO (2000)
The effect of kaolin particles on the bacterial activity as well as on the efficacy of a biocide was investigated. The results show that the presence of the clay particles enhance the Pseudomonas fluorescens activity for all buffered pH values tested, this increase being more relevant for the more adverse pH for this bacteria growth. The results also demonstrated that kaolin reduces the ability of desinfection of a carbamate-based biocide against P. fluorescens suspensions.